Web applications : how to effectively use apps in your marketing - Tasner, Michael, 1984- (FTPress Delivers elements., 2011)
This Element is an excerpt from Marketing in the Moment: The Practical Guide to Using Web 3.0 Marketing to Reach Your Customers First (9780137081097) by Michael Tasner. Available in print and digital formats. Use the newest smartphone, Facebook, and Google apps to supercharge your Web 3.0 marketing strategies and tactics. The term apps has come to refer specifically to small programs found on iPhones and other smartphones, Facebook, and Google. They typically help you do something and make life a little easier in a big way. The development of apps has recently grown at an extraordinary rate. Even more significant is their use for Web 3.0 sites and marketing tactics....